Strength Analysis of Steel Construction and Swing Hanger Using Theoretical Method and Simulation of Finite Element - Effendi, Riki; Maghfurah, Fadwah (University of Muhammadiyah Malang, 2019)
The initial activity in this study was carried out by examining the results of testing of reinforcing steel through tensile testing and bending testing. The study focused on the stress analysis of the test material to determine and classify the test material with SNI reference which applies as a condition for the application of test material to a construction. The material tested was a type of Fin Reinforcing Steel (BjTS 40) with diameters of 10 mm, 13 mm, 16 mm, 19 mm and 22 mm respectively with each sample 2 specimens. In tensile and bending tests, the test results will be known the load of the test material when tested at the yield point and at the maximum point, according to the strain stress graph illustrated. The results of the scale of the test machine are then recorded to perform stress analysis. The test results data are then used to calculate the amount of stress that occurs in the test material. Stess analysis is carried out on the swing hanger as well as construction steel samples. Stress analysis uses theoretical stress analysis methods and finite element simulation methods using computer work program simulation CAD / CAE technology solidworks. From the results of theoretical calculations, it is known that the amount of stress that occurs, the yield strength limit of the material and also the safety factor of the test material, both on the swing hanger test material and also the construction steel test sample. Furthermore, the initial data of the swing hanger test material as well as steel construction were carried out modeling by using a solidworks computer work program application. While the results of solidwork modeling are then analyzed by finite element simulation and known the magnitude of stress, strain, loading buckling that occurs and also the visualization of the material characteristics of the load treatment.